-1/2 : (4x - 1) +3 = -5

-1/2 : (4x - 1) +3 = -5
Câu trả lời này dùng AI, hãy kiểm tra lại trước khi sử dụng
To solve the equation \(-\frac{1}{2}(4x - 1) + 3 = -5\), we follow these steps:

1. Multiply both sides by -2 to eliminate the fraction:
\(-\frac{1}{2}(4x - 1)\) becomes \(4x - 1\)
So, multiplying by -2 gives:
\(-(4x - 1) + 6 = 10\) (since -23 = -6 and -2(-5) = 10)

2. Distribute the negative sign inside the parentheses:
\(-4x + 1 + 6 = 10\)

3. Combine like terms:
\(-4x + 7 = 10\)

4. Isolate the variable \(x\):
Subtract 7 from both sides:
\(-4x = 3\)

5. Divide by -4:
\(x = -\frac{3}{4}\)

So the solution to the equation is \(x = -\frac{3}{4}\).
Đăng phản hồi